2005
DOI: 10.1242/jcs.02545
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II subunit 3 is retained in the cytoplasm by its interaction with HCR, the psoriasis vulgaris candidate gene product

Abstract: Here, we show that the subcellular localization of α-like RNA polymerase II core subunit 3 (RPB3) is regulated during muscle differentiation. We have recently demonstrated that the expression of RPB3 is regulated during muscle differentiation and that, inside RNA polymerase II (RNAP II), it is directly involved in contacting regulatory proteins such as the myogenic transcription factor Myogenin and activating transcription factor ATF4. We show for the first time, that RPB3, in addition to its presence and role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The fluorescence revealed that the expression pattern of CCHCR1 consists in punctuated signals throughout the cytoplasm. This distribution is coherent with observations made in other cell lines [21], [22] and with its endogenous expression pattern [23]. The E2 protein from HPV16 displays a diffuse expression pattern primarily concentrated in the nucleus and also present in the cytoplasm as previously described [24].…”
Section: Resultssupporting
confidence: 91%
“…The fluorescence revealed that the expression pattern of CCHCR1 consists in punctuated signals throughout the cytoplasm. This distribution is coherent with observations made in other cell lines [21], [22] and with its endogenous expression pattern [23]. The E2 protein from HPV16 displays a diffuse expression pattern primarily concentrated in the nucleus and also present in the cytoplasm as previously described [24].…”
Section: Resultssupporting
confidence: 91%
“…Of an estimated 2.5×10 6 transformants, 30 clones proliferated on media lacking histidine and adenine as well as stained positive for β-galactosidase. Several clones were isolated for further characterisation [6], [9][10] and the clone encoding for the ubiquitous eukaryotic translation elongation factor 1 gamma subunit (eEF1γ) (fig. 1B) was selected for further study.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cells were co-transfected with myc-eEF1γ and a series of RPB3 deletion mutants fused to the EGFP protein (fig. 2A) [10]. Immunoprecipitation was performed with an anti-myc monoclonal antibody and analysed by western blot using an anti-EGFP monoclonal antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A regtilator>' role forCCHCRl in transcription factor binding has been discovered recently (17). HCR transgenic mice having either the huinan non-risk HCr< allele or the psoriasis risk allele showed altered cutaneous expression profiles for several proteins known to be upregtilated in human psoriasis, such as keratins 6, 16, and 17, tenascin C. and certain SPRRs and matrix metalloproteinases (18).…”
mentioning
confidence: 99%